Pharmacological activity of the hydroalcoholic extract from Hovenia dulcis thunberg fruit and the flavonoid dihydromyricetin during hypercholesterolemia induced in rats - Juliana Tensol Pinto; Tânia Toledo de Oliveira; Luana Farah Alvarenga; Adriano Simões Barbosa; Virgínia Ramos Pizziolo; Marcelo Rocha da Costa (Universidade de São Paulo, 2014)
Cerebrovascular accidents and coronary artery disease are the leading causes of cardiovascular mortalities in Brazil and high levels of LDL cholesterol are one of the main risk factors. In this context, several plant extracts and natural substances have shown promise as cholesterol-lowering. The objective of this study was to evaluate the potential of the hydroalcoholic extract of the fruit of H. dulcisand of dihydromyricetin in cholesterol reduction in hypercholesterolemic rats. Forty-two Wistar male rats were distributed into seven groups of six animals that received diets supplemented with 1% cholesterol and 0.3% cholic acid, with the exception of the control group, which received conventional diets. Animals were treated with oral suspensions containing: atorvastatin 1.0 mg/kg; H. dulcisextract at 50.0 and 100.0 mg/kg and dihydromyricetin at 25.0 and 50.0 mg/kg vehicle (control group). The following biochemical markers were evaluated; total cholesterol, HDL-C, LDL-C, triglycerides, AST, ALT, and alkaline phosphatase. The hypercholesterolemic diet was effective in inducing hypercholesterolemia, increasing total cholesterol by 112.7% relative to the control group. The treatments with two doses of the extract proved to be promising hypocholesterolemic agents, as they were able to substantially reduce total cholesterol and LDL-C, without significantly altering triglycerides, hepatic transaminases, and alkaline phosphatase, thereby encouraging the studies with the plant H. dulcis. The groups treated with the flavonoid dihydromyricetin, although they showed a significant reduction in total cholesterol and LDL-C, and found increases in triglycerides and hepatic transaminases, which is unwanted in the context of hypercholesterolaemia.